Exploring how to improve access to psychological therapies on acute mental health wards from the perspectives of patients, families and mental health staff: qualitative study. Issue 4 (14th July 2022) - Berry, Katherine; Raphael, Jessica; Haddock, Gillian; Bucci, Sandra; Price, Owen; Lovell, Karina; Drake, Richard J.; Clayton, Jade; Penn, Georgia; Edge, Dawn
Abstract : Background: Psychological therapy is core component of mental healthcare. However, many people with severe mental illnesses do not receive therapy, particularly in acute mental health settings. Aims: This study identifies barriers to delivering and accessing psychological therapies in acute mental health settings, and is the first to recommend how services can increase access from the perspectives of different stakeholders (staff, patients and carers). Method: Sixty participants with experiences of acute mental health wards (26 staff, 22 patients and 12 carers) were interviewed about barriers to accessing therapy in in-patient settings and how therapies should be delivered to maximise access. Results: Four themes were identified: (a) 'Models of care', including the function of in-patient wards, beliefs about the causes of mental health problems and the importance of strong leadership to support psychosocial interventions; (b) 'Integrated care', including the importance of psychologists being ward-based, as well as having strong links with community teams; (c) 'Acute levels of distress', including factors that aggravate or ameliorate the impact of this on engagement in therapy; and (d) 'Enhancing staff capability and motivation', which is influenced by contextual issues. Conclusions: It is possible to improve access to therapy through strong leadership (that is supportive of talking treatments), flexible delivery of therapy (that considers short admissions) and a whole-systems approach that promotes ward staff understanding of the psychosocial causes of mental illness and staff well-being. It is essential to ensure continuity between in-patient and community therapy services, and for wards to have physical space to carry out therapy.